Regulatory role of DBC1 in inflammation and autoimmune diseases - Jinzhi Wu; Fan Yang; Guanhua Xu; Xinlei Ma; Jin Lin; Weiqian Chen (Rheumatology & Autoimmunity)
Abstract Deleted in breast cancer 1 (DBC1) is a nuclear protein that plays an important role in apoptosis, DNA repair, and epigenetic modifications. Extensive studies have highlighted the importance of DBC1 in tumorigenesis. Surprisingly, it was recently found that DBC1 works as an immune regulator in the immune system and in autoimmune diseases. This study systematically reviewed how DBC1 exerts its function and assumed a possible role of DBC1 in autoimmunity. The search strategy included the following terms: (1) (DBC1) OR (CCAR2) and (2) ((DBC1) OR (CCAR2)) AND ((immunity) OR (autoimmune diseases)). The above terms were entered into PUBMED, covering the period from 2002 to 2024, and articles investigating or involving functional studies of DBC1 were evaluated. Subsequently, a systematic review was conducted to investigate the potential role of DBC1 in autoimmunity. Our findings indicate that DBC1 exhibits dual pro‐inflammatory and anti‐inflammatory functions, primarily achieved through the direct or indirect modulation of key immunoinflammatory proteins, including silent information regulation 2 homolog‐1, histone deacetylase 3, SUVH9, and signal transducer and activator of transcription (STAT). DBC1 influences cytokine production and immune cell activity. However, most of these studies were based on oncological diseases, and direct exploration of the role of DBC1 in autoimmune diseases remains limited. Further research is necessary to fully understand the precise immunomodulatory function of DBC1 in autoimmune diseases, as well as its underlying mechanism and physiological effects. In conclusion, DBC1 regulates apoptosis, autophagy, aging, and epigenetic modifications, can potentially be an upstream molecule of the Janus kinase/STAT signaling pathway, and is worthy of further comprehensive and in‐depth evaluation.